Models of Corporate Criminal Liability in Comparative Law - Cristina de Maglie (Washington University Global Studies Law Review, 2005)
This Article considers modern systems of criminal justice and the different models of assessing responsibility for crimes committed to benefit corporate interests. The analysis is two-pronged. First, this piece examines systems that have adopted the principle of corporate criminal liability. Within this category, a further important distinction must be made between the most evolved models, which have accepted a requirement of corporate culpability, and those models that reject the idea of an organizational mens rea, imposing instead various corporate liabilities without any separate measure of corporate blameworthiness. Second, this piece considers those models that reject the principle of corporate criminal liability and are restricted to the use of extra-criminal mechanisms for the regulation of corporate crime.
Keywords: Comparative law; Juristic persons criminal liability; United States